Kontribusi Talent Acquisition Di Hashmicro Dalam Program MBKM Periode 2022 - Yunius Yunius; Muhammad Ghazi; Agustinus Sri Wahyudi; Nurti Widayati (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
This internship report was prepared to explain the author's experience in participating in the Independent Learning-Independent Campus (MBKM) program at Hashmicro. In this program, the author has the opportunity to become a Talent Acquisition Intern and is responsible for recruitment activities from the marketing department and business development department positions. This report will consist of three sections, including an introduction (containing the background of the participation and responsibilities of the author in the MBKM program), analysis and discussion (containing repetitive routine activities, non-routine activities, and skills and knowledge utilized and acquired during the program MBKM is in progress), and closing (contains conclusions, limitations, and the author's recommendations for this MBKM program)